Fluorescence-Detected Linear Dichroism of Wood Cell Walls in Juvenile Serbian Spruce: Estimation of Compression Wood Severity. (9th February 2016) - Savić, Aleksandar; Mitrović, Aleksandra; Donaldson, Lloyd; Simonović Radosavljević, Jasna; Bogdanović Pristov, Jelena; Steinbach, Gabor; Garab, Győző; Radotić, Ksenija
Abstract: Fluorescence-detected linear dichroism (FDLD) microscopy provides observation of structural order in a microscopic sample and its expression in numerical terms, enabling both quantitative and qualitative comparison among different samples. We applied FDLD microscopy to compare the distribution and alignment of cellulose fibrils in cell walls of compression wood (CW) and normal wood (NW) on stem cross-sections of juvenile Picea omorika trees. Our data indicate a decrease in cellulose fibril order in CW compared with NW. Radial and tangential walls differ considerably in both NW and CW. In radial walls, cellulose fibril order shows a gradual decrease from NW to severe CW, in line with the increase in CW severity. This indicates that FDLD analysis of cellulose fibril order in radial cell walls is a valuable method for estimation of CW severity.